Ability for self-care in clients undergoing antineoplastic chemotherapy treatment (Bioscience Journal, 2020)
To identify the self-care capacity of cancer clients treated at the chemotherapy service of a university hospital in Minas Gerais/Brazil. This is a cross-sectional study conducted with 79 adult and elderly participants diagnosed with primary cancer on antineoplastic chemotherapy treatment. Two instruments were used to achieve the proposed objective, one created by the authors for sociodemographic characterization and another translated, adapted and validated to Brazilian Portuguese to assess the capacity of self-care, namely, the Appraisal of Self Care Agency Scale-Revised, the ASAS-R. Most respondents were female (50.6%), married (58.2%), had between five and nine years of schooling (43.0%), had a family income of one to three minimum wages (86.1%) and were predominantly elderly (54.4%). The mean score obtained for self-care capacity was 57.8. A dichotomy between the patients' usual chores and their diagnoses was observed, but the participants also stated that they dedicate time and were willing to take care of their health. They also stated that they looked for the best ways to take care of themselves and sought updated information whenever necessary, although no statistically significant association was found between self-care scores and sociodemographic variables. This study allowed to show that sociodemographic variables such as education, income, religion and cohabitation should be taken into account by health professionals to favor the client's engagement in self-care actions.